Achieved low-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio predicts the pathophysiological evolution of lipid-rich plaques in acute coronary syndromes: an optical coherence tomography study - He, Luping; Yi, Boling; Zhang, Dirui; Hu, Sining; Zhao, Chen; Sun, Rui; Ma, Jianlin; Hou, Jingbo; Jia, Haibo; Ma, Lijia; Yu, Bo (Frontiers in Cardiovascular Medicine, 2023)
Background: As a novel lipoprotein ratio, baseline low-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (LHR) is closely related to the clinical outcomes of acute coronary syndromes (ACS) after percutaneous coronary intervention. However, the pathophysiological impact of achieved LHR (aLHR) on the evolution of non-culprit lipid rich plaques has not been systematically explored. Methods: Between September 2013 and December 2018, ACS patients with both baseline and 1-year follow-up optical coherence tomography (OCT) examinations were included in current study. They were divided into two groups according to the median value of aLHR at 1 year. Results: Overall, 132 patients with 215 lipid rich plaques were enrolled, with a median aLHR: 1.62. There were thinner fibrous cap thickness (FCT) (133.3 [70.0-180.0] μm vs. 160.0 [100.0-208.3] μm, p = 0.025) and higher prevalence of thin-cap fibroatheroma (TCFA) (24 [22.4%] vs. 13 [12.0%], p = 0.044) and CLIMA-defined high-risk plaques (12 [11.2%] vs. 3[2.8%], p = 0.015) in the high aLHR group. Compared with other serum lipid indexes, aLHR showed the best robust correlation with the evolution of plaque vulnerability in both unadjusted and adjusted analyses. Cut-off value of aLHR to predict the progression of maximal lipid arc and FCT was 1.51. In the adjusted model, aLHR ≥1.51 was an independent predictor of TCFA (odds ratio [OR]: 3.008, 95% CI: 1.370 to 6.605, p=0.006) at 1 year. Conclusions: aLHR correlates well with the evolution of lipid rich plaques and vulnerable phenotypes at 1-year follow-up, which might be an important and convenient serum indicator in the secondary prevention of ACS.